SISTEM INFORMASI MANAJEMEN MITRA DI BADAN PUSAT STATISTIK (BPS) KABUPATEN MINAHASA BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING (XP) - Laode Muhamad Ikhlas; Olivia Kembuan (Komunitas Menulis dan Meneliti (Kolibi), 2023)
The utilization of technology in government agencies has become a primary foundation for advancing and improving efficiency in services. In Indonesia, the Central Statistics Agency (BPS) serves as a model for implementing advanced information technology to enhance the quality of services and responsiveness to the needs of the community. This research specifically focuses on the development of the Partner Management Information System within the BPS Minahasa District in response to the absence of a similar system at the district level. During surveys and censuses, BPS Minahasa faces challenges in partner data management due to reliance on applications provided by the Central BPS. To address these issues, this research proposes a solution through the development of a Partner Management Information System using the